Investigation of the mechanism of C(sp3)-H bond cleavage in Pd(0)-catalyzed intramolecular alkane arylation adjacent to amides and sulfonamides. - Rousseaux, S; Gorelsky, S; Chung, B; Fagnou, K (2010)
The reactivity of C(sp(3))-H bonds adjacent to a nitrogen atom can be tuned to allow intramolecular alkane arylation under Pd(0) catalysis. Diminishing the Lewis basicity of the nitrogen lone pair is crucial for this catalytic activity. A range of N-methylamides and sulfonamides react exclusively at primary C(sp(3))-H bonds to afford the products of alkane arylation in good yields. The isolation of a Pd(II) reaction intermediate has enabled an evaluation of the reaction mechanism with a focus on the role of the bases in the C(sp(3))-H bond cleaving step. The results of these stoichiometric studies, together with kinetic isotope effect experiments, provide rare experimental support for a concerted metalation-deprotonation (CMD) transition state, which has previously been proposed in alkane C(sp(3))-H arylation. Moreover, DFT calculations have uncovered the additional role of the pivalate additive as a promoter of phosphine dissociation from the Pd(II) intermediate, enabling the CMD transition state. Finally, kinetic studies were performed, revealing the reaction rate expression and its relationship with the concentration of pivalate.